Prolonged P-wave Dispersion Increases Risk of Perioperative Atrial Fibrillation After CABG Surgery - Yuwono, Jiauw, Davinarta; Ardhianto, Pipin; Bahrudin, Udin; Uddin, Ilham (Medica Hospitalia : Journal of Clinical Medicine, 2026)
BACKGROUND : Postoperative Atrial Fibrillation (POAF) is a secondary Atrial Fibrillation caused by cardiac surgical intervention, especially Coronary Artery Bypass Graft (CABG) Surgery. P-wave dispersion (Pdis) represents the difference between the maximum and minimum P-wave durations obtained from a standard 12-lead ECG. P-wave dispersion is considered a non-invasive ECG marker of atrial remodeling and may predict the occurrence of atrial fibrillation. AIMS : This study analyzes the association between P-wave dispersion and Perioperative Atrial Fibrillation after Coronary Artery Bypass Graft Surgery. METHOD : This was an observational, analytic study with a retrospective design. The total number of subjects was 48 patients, divided into the POAF group (n=24) and no POAF group (n=24). Demographic data and preoperative ECG records were obtained from the patient's medical records. The significance of P-wave dispersion was analyzed using independent t-test and logistic regression. The Receiver Operating Characteristic (ROC) test was used to define cut-off values, sensitivity, and specificity of P-wave dispersion. RESULT : The total number of subjects in this study was 48 patients, consisting of 43 men and five women. The mean age of the patients was 57.85 ± 5.83 years. The mean P-wave dispersion was higher in patients who experienced POAF (64.97 ± 13.21 vs. 50.55 ± 7.14; p<0.001). P-wave Dispersion was significantly associated with the incidence of POAF (p<0.001; cut-off 55.65 ms; OR 9.00; 95% CI 2.437-33.244). CONCLUSION : P-wave Dispersion is significantly associated with Postoperative Atrial Fibrillation. P-wave dispersion value greater than 55.65 ms increases the risk of POAF after CABG by 9-fold.